An international survey on the clinical use of rigid and deformable image registration in radiotherapy. Issue 10 (11th September 2020) - Yuen, Johnson; Barber, Jeffrey; Ralston, Anna; Gray, Alison; Walker, Amy; Hardcastle, Nicholas; Schmidt, Laurel; Harrison, Kristie; Poder, Joel; Sykes, Jonathan R.; Jameson, Michael G.
Abstract: Objectives: Rigid image registration (RIR) and deformable image registration (DIR) are widely used in radiotherapy. This project aims to capture current international approaches to image registration. Methods: A survey was designed to identify variations in use, resources, implementation, and decision‐making criteria for clinical image registration. This was distributed to radiotherapy centers internationally in 2018. Results: There were 57 responses internationally, from the Americas (46%), Australia/New Zealand (32%), Europe (12%), and Asia (10%). Rigid image registration and DIR were used clinically for computed tomography (CT)‐CT registration (96% and 51%, respectively), followed by CT‐PET (81% and 47%), CT‐CBCT (84% and 19%), CT‐MR (93% and 19%), MR‐MR (49% and 5%), and CT‐US (9% and 0%). Respondent centers performed DIR using dedicated software (75%) and treatment planning systems (29%), with 84% having some form of DIR software. Centers have clinically implemented DIR for atlas‐based segmentation (47%), multi‐modality treatment planning (65%), and dose deformation (63%). The clinical use of DIR for multi‐modality treatment planning and accounting for retreatments was considered to have the highest benefit‐to‐risk ratio (69% and 67%, respectively). Conclusions: This survey data provides useful insights on where, when, and how image registration has been implemented in radiotherapy centers around the world. DIR is mainly in clinical use for CT‐CT (51%) and CT‐PET (47%) for the head and neck (43–57% over all use cases) region. The highest benefit‐risk ratio for clinical use of DIR was for multi‐modality treatment planning and accounting for retreatments, which also had higher clinical use than for adaptive radiotherapy and atlas‐based segmentation.